THE INFLUENCE OF THE USE OF GADGETS ON LEARNING INTERESTS AND LEARNING ACHIEVEMENTS OF STUDENTS IN THE STUDY OF ISLAMIC RELIGION EDUCATION IN UPT SPF SMP NEGERI 52 MAKASSAR CITY - Mulyadi, Wahdini Nur; Muslimin, Abdul Azis; Sumiati, Sumiati (JICSA : Journal of Islamic Civilization in Southeast Asian, 2024)
This research aims to examine the influence of gadget use on students' interest in learning and learning achievement in Islamic religious education subjects at UPT SPF SMP Negeri 52 Makassar City. The research method used is quantitative research and uses an associative quantitative approach. The data collection methods used are observation, questionnaires, and documentation. Data analysis techniques are descriptive analysis, prerequisite analysis, and inferential analysis. The population of this study is class IX A and using a saturated sample, the entire research sample is from the total population, namely class IX A with a total of 30 students. The research results obtained related to the influence of the use of gadgets on students' learning interest and learning achievement in Islamic religious education subjects at UPT SPF SMP Negeri 52 Makassar City, namely: (1) the significance value obtained is that the use of gadgets with the value of students' learning interest has a value significant 0.591 > 0.05, so it can be said that between the value of using the gadget and the value of students' learning interest there is a significant influence. (2) the significance value obtained is a significant increase based on the value of using the gadget and the value of the student's learning achievement has a significant value of 0.305 > 0.05, so it can be said that there is a significant influence between the value of using gadgets and the value of students' learning achievement. (3) The results of the MANOVA test analysis show the influence of gadget use on students' interest in learning and learning achievement at UPT SPF SMP Negeri 52 Kota Makassar, the results of the Manova Tests of Between-Subjects Effects on the influence of gadget use on students' interest and learning achievement show that there is an influence indicated by the value of ???. 0.028 < 0.05 and 0.021 < 0.05 use of gadgets on interest and learning achievement of UPT SPF students at SMP Negeri 52 Makassar City.